Penerapan Kelembagaan Operasi Pemeliharaan untuk Jaringan Irigasi pada Masyarakat Lokal - Lumongga, Retta Ida (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
The construction of sprinkler irrigation indryland farming operation could be delayed due to the absence of the formal institution of farmer group, who participate to perform maintenance operation. What is the right institutional forms of irrigation in conformity with the local conditions and local wisdom in dryland farming is a problem addressed by this study. The application on trial of the institutional of participation of the communities in the maintenance operations carried out on two selected provinces that both have a dry climate criteria and big gun sprinkler has not been operated, namely Desa Linelean, Districts Modoinding, North Sulawesi Province, and Desa Manusak and Desa Oesao, Districts East Kupang, East Nusa Tenggara Province. Qualitative approach is used. As a result, the organizational structure is possible to be made simpler, where jurupungut can be optionally adjusted to conditions at the application site. Conclusion, the application of institutional outline can be implemented according to the stages that have been there, however its application is not absolute, but rather, it takes an adjustment to the characteristics and local wisdom.